"PI-JAK" Tax Smart Community: Tax Literacy of PP No. 58 Year 2023 for Gunung Gangsir Village - Alif Faruqi Febri Yanto; Tomy Rizky Izzalqurny; Nabilla Carissa Ratnadewati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Tax socialization in Gunung Gangsir Village is an effort to increase awareness and compliance of taxpayers, especially on the understanding of Income Tax Article 21 listed in PP No. 58 of 2023 through the use of science and technology. This program uses various educational methods, such as social media, websites, mobile applications, animated videos, and infographics, to reach and provide maximum understanding to the community. An interactive and participatory education approach is also applied to increase villagers' understanding and participation. Taxpayer profile mapping and compliance data analysis helped identify target audiences and factors influencing compliance. The success of this program can be seen from several indicators, namely: increased awareness of villagers about the importance of taxes, increased understanding of the types of taxes and procedures for paying PPh Pasal 21 tax listed in PP No 58 of 2023, increased taxpayer compliance in Gunung Gangsir Village, and increased village revenue. This program is expected to serve as an example and inspiration for other villages in Indonesia to increase taxpayer awareness and compliance, as well as encourage an increase in village revenue and community welfare.